Use of acupuncture among chronic disease patients attending primary healthcare facilities: a cross-sectional study in Korea - Su Yeon Lee; Soo Jeung Choi; Hyea Bin Im; Dain Choi; Dongwoon Han (BMC Complementary Medicine and Therapies)
Abstract Background Given the crucial role of integrating acupuncture treatment into primary care for managing chronic diseases, this study endeavors to identify the utilization of acupuncture among chronic disease patients seeking primary care services in Korea. Additionally, it aims to evaluate their knowledge level and perceptions related to acupuncture use. Methods A descriptive cross-sectional study was conducted among chronic disease patients attending a primary care clinic in Korea. A self-reported questionnaire comprising 37 items was employed to evaluate the utilization of acupuncture treatment. These items covered socio-demographic information, respondents’ health status, levels of acupuncture knowledge, and patterns of acupuncture use. Using the SPSS Statistics 26.0 Network Version program, descriptive statistics, a chi-square test, and a logistic regression analysis were performed to identify factors associated with acupuncture treatment. Results Out of 370 respondents, 44.3% reported utilizing acupuncture treatment. The most popular reason for the utilization of acupuncture was to enhance the effectiveness of the current treatment. The patients with musculoskeletal disease had the highest utilization rate of 53.2%. The main source of information for acupuncture use was family and friends. The average score for the level of knowledge on acupuncture treatment among the respondents was 65.4%, and the knowledge level of the acupuncture group was high. Potential predictors of acupuncture use included musculoskeletal disease, and intention to recommend acupuncture. Conclusion This study highlights the widespread acceptance of acupuncture use among patients with chronic diseases in primary healthcare context. Integration of acupuncture into primary care emerges as a viable avenue for effective chronic disease management, and fostering a comprehensive and holistic approach to healthcare. Clinical trial number Not applicable.